Continuous photobleaching to study the growth modes of focal adhesions - Beer, Alex G. F. de; Majer, Günter; Roke, Sylvie; Spatz, Joachim P. (Journal of adhesion science and technology, 2010)
We combine total internal reflection fluorescence microscopy with continuous photobleaching to study the growth mode of focal adhesions in rat embryonic fibroblasts (REF-52). We measured GFP-labelled β3 integrin, which exhibits a diffusion rate of 10-14-10-13 m2/s when it is not bound to a focal adhesion. We show that exchange of β3 integrin between focal adhesions and the surrounding membrane occurs only at the edges of the focal adhesion. We, therefore, conclude that focal adhesions show an edge-on/edge-off growth, in contrast to the bulk-on/bulk-off growth mode that is assumed in many theoretical treatments.
Online veröffentlicht: 02 April 2012
Gesehen am 04.09.2023